A Sociolinguistic Study of the Emerging Trends in Igbo Personal Names - Nnamdi-Eruchalu, Geraldine Ifesinachi (Advances in Social Sciences Research Journal, 2018)
Ideally, personal names reflect the ideology, beliefs, values and norms of the bearers, and as such, an embodiment of their social identity. The current wave of westernization sweeping across Africa, especially the Igbo society, has influenced all aspects of her culture, including naming. Some of the names which were once regarded as nicknames have since been transformed to personal names, thus calling for scholarly investigations. The researcher argues that some of the current trends in naming stripe the names of their cultural, social, religious and political relevance, and blot the identity of the bearers, while others violate the norms of naming in Igbo culture. To provide the bases for comparison, the researcher compiled regular and trending Igbo names from her personal contacts in Awka, Anambra State, Nigeria, as well as from the social media, television and radio broadcasts, the internet and the print media for a descriptive analysis. Interview was also incorporated to obtain from the bearers of the names deeper insights into the motivation behind the names. It was observed that some Igbo names no longer have any meaning relationships with their derivatives, while others have experienced different levels of westernization. It is recommended that awareness campaigns should be deployed to educate the people on the inter-connectivity of names, language, culture and identity so that they can place meaningfulness and relevance above fashion when it comes to personal names.